Emotive Classification of Lexical Units of Students’ Sociolect - Davlyatova Gulchekhra Nasirovna; Akramova Nozima Muzaffarovna (Zien Journals, 2022)
The article under discussion reveals emotive classification of lexical units of students’ sociolect. The author of the article considers that students’ sociolect is characterized by highly expressive vocabulary which is inherent in corporate youth sociolects, in particular it concerns emotional shades in youth speech. In some cases, emotional words and expressions can convey the speaker's attitude towards a fact of reality more clearly: according to a number of motifs, we can say that they are expressions of generally positive or generally negative emotions.
Keywords: Students; sociolect; youth speech; motifs